Musculoskeletal disorders and related risk factors among Iranian farmers: applying Protection Motivation Theory (International Journal of Occupational Safety and Health, 2024)
Introduction: Musculoskeletal disorders (MSDs) are one of the main occupational health problems worldwide. Among different careers, the farming profession is highly prone to MSDs. A variety of factors to prevent MSDs can be named such as preventive behaviors. To determine the factors in health-related behaviors, protection motivation theory (PMT) is widely accepted as a framework. Therefore, the present study is an attempt to determine the MSD preventive factors using PMT in farmers in rural areas of Tuyserkan County.Methods: This was a cross-sectional study among 285 farmers living in Tuyserkan County in 2021. The farmers were selected through cluster random sampling from 54 health houses affiliated with the health center of the county. In the next stage, the participants were selected through simple random sampling. Data gathering was done online using a questionnaire of the constructs of PMT and a Nordic questionnaire. The collected data were analyzed in SPSS 24 using linear and binary regression tests.Results: The mean work experience of the farmers was 22.11 years, and the activity in 81.8% of the participants was in standing and sitting positions. In addition, 55.4% of the participants had at least one of the MSD symptoms and the most common symptoms were back pain (67%) and pain in the knee area (35.5%). The majority of farmers did not observe MSD alleviation behaviors. The variables perceived susceptibility, fear, self-efficacy, and behavior had protective effects against MSDs in the farmers; while, monthly income, age, work hours per day, and type of activity had intensifying effects on MSDs. Conclusions: Farming is recognized as a risky job for health and several evidences show a relationship between failure to perform preventive behaviors and the prevalence of MSDs. Given the paucity of studies using health education theories and models to examine the factors in MSDs, the present study employed the PMT framework to examine MSD factors in farmers.